Camptothecin prodrug nanomicelle based on a boronate ester-linked diblock copolymer as the carrier of doxorubicin with enhanced cellular uptake. Issue 2 (22nd January 2018) - Gao, Ya; Xiao, Yi; Liu, Shiyuan; Yu, Jiahui
Abstract: A novel pH-sensitive polymeric prodrug of camptothecin (CPT) by polymerizing γ-camptothecin-glutamate N-carboxyanhydride (Glu (CPT)-NCA) on boronate ester-linked poly (ethyleneglycol) (PEG) directly via the amine-initiated ring open polymerization (ROP) has been developed. The resulting amphiphilic prodrug (mPEG-BC-PGluCPT) could self-assemble into nanoparticles and encapsulate doxorubicin (Dox) simultaneously in aqueous solution for dual-drug delivery. The formation of polymeric prodrug micelles (mPEG-BC@PGluCPT) was confirmed by the measurements of critical aggregation concentration (CAC), particle size, and morphology observations. The mPEG-BC@PGluCPT micelles were colloidally stable in solutions for two weeks. Polymeric prodrug micelles mPEG-BC@PGluCPT and Dox-loaded micelles mPEG-BC@PGluCPT⋅Dox showed sustained drug release profiles over 48 h. As expected, drug release was accelerated by the decreasement of pH value from 7.4 to 6.0, which demonstrated pH-dependent manner of drug release. Additionally, it was found that cellular uptake of mPEG-BC@PGluCPT⋅Dox micelles on HepG2 cells was higher than that on HL-7702 cells, especially in culture medium at pH 6.0. The enhanced cellular uptake of mPEG-BC@PGluCPT⋅Dox micelles under acidic condition on HepG2 cells resulted in the higher cytotoxicity of mPEG-BC@PGluCPT⋅Dox micelles at acidic pH than that at pH 7.4.